The Difference of Results in Abdomen and Anus Area Measurement With Non-Contact Infrared Thermometer - Veterini, Anna Surgean; Rehatta, Nancy Margarita; Hamzah, Hamzah; Widijiati, Widijiati; Sarmanu, Sarmanu; Soedarmo, Subijanto Marto; Pudjirahardjo, Widodo Jatim; Adi, Annis Catur; Rachmawati, Heni; Sudiana, I Ketut (Jurnal Veteriner; Vol 22 No 2 (2021), 2021)
Study about sepsis is chalenging to get the right therapeutic method. One clinical signs of the sepsis mice model is changes in body temperature. An easy way to examine body temperature is using infrared non-contact thermometer. The aim of this study is to compare the body temperature obtained from infrared non-contact thermometer at the abdomen and anus area. We used male Mus musculus mice, body weight of 25–30 grams, were divided into 2 groups (control and treated groups). In the control group, mice were injected with NaCl 0.9% solution, with the amount of NaCl volume equal to LPS. In the treated group, mice were injected with 2.5 mg/kgBW of LPS intraperitoneally. Body temperature measurement was measured in abdomen (t abd ) and anus (t an ) area. Body temperature was measured at 8 th  and 24 th hour after LPS or NaCl injection. Body temperature value result using t abd was higher than t an . LPS injection to mice produced an increase in body temperature but was not significant when compared to the control group (8 th and 24 th hour). The mean difference between t abd and t an in 8 th hour control groups respectively were 2.12 o C. The mean difference between t abd and t an in 24 th hour control groups 4.6 o C. The mean difference in treated groups (8 th hour) was 4.66 o C, while it was 4.77 o C in the 24 th hour  treated groups. LPS could caused vasodilation of the vessels, the measurement area of non contact-infrared thermometer will be the most important factor to be considered; t an may closer to the physiology condition.